1995
DOI: 10.1093/humrep/10.1.132
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal status of uni-pronuclear human zygotes following in-vitro fertilization and intracytoplasmic sperm injection

Abstract: Uni-pronuclear embryos (n = 42) were analysed by fluorescence in-situ hybridization (FISH) with two to four chromosome pair-specific probes. Half of these embryos resulted from conventional insemination and half from intracytoplasmic sperm injection (ICSI). The majority of uni-pronuclear embryos from conventional insemination were normally diploid (61.9%) whereas only 9.5% of uni-pronuclear ICSI embryos (P < 0.001) were diploid. In addition, a significantly higher number of uni-pronuclear embryos from conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
56
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 0 publications
7
56
1
Order By: Relevance
“…Resultant diploid embryos were previously confirmed to undergo predominantly normal fertilization owing to the asynchronous formation of two pronuclei [19,21], and a normal diploid hESC line has been derived from these oocytes [28]. These results coincide with our unpublished data, which show that, out of 16 hESC lines that are derived from one-pronuclear oocytes, the majority were of biparental origin.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Resultant diploid embryos were previously confirmed to undergo predominantly normal fertilization owing to the asynchronous formation of two pronuclei [19,21], and a normal diploid hESC line has been derived from these oocytes [28]. These results coincide with our unpublished data, which show that, out of 16 hESC lines that are derived from one-pronuclear oocytes, the majority were of biparental origin.…”
Section: Discussionsupporting
confidence: 87%
“…With the widespread introduction of assisted reproductive technology (ART), human oocytes can be manipulated and fertilized in vitro. It is suggested that suboptimal conditions [18], intracytoplasmic sperm injections [19] and cryopreservation [20] might parthenoactivate human oocytes. In most cases, spontaneous parthenogenesis is designated by onepronucleus formation, and the resulting embryos should never be transferred back into the patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientific literature has shown that 16% of morphologically normal embryos on day transfer has exhibited chromosomal abnormalities in patients who are 20-34 years old, 37% in patients who are 35-39 years old, and over 50% when the maternal age is 40-45 years (18,37,38). Special situations required other methods of embryos assessment, such as PGD.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, because of the uncertainty of their genetic normality, transferring such embryos is controversial among ART laboratories. The etiology of zygotes forming with 1PN remains unknown; however, several plausible mechanisms have been proposed after IVF or ICSI as follows- (1) parthenogenetic activation [24,26,33,34], (2) asynchronous formation of male PN (mPN) and fPN [24,34,35], and (3) early fusion of both PN prior to syngamy [36]. In addition, we observed additional PB-like substance extruded into the perivitelline space after the 2nd PB extrusion, forming zygotes carrying a single PN (manuscript in preparation).…”
Section: Aberrant Behavior Of Female Pn (Fpn) During the Pronuclear Smentioning
confidence: 99%